Construction and Demolition Waste Management in Urban Transformation: A Case Study for Performance Evaluation - Yazgan, Ogulcan; Ozturkoglu, Yucel; Ozkan-Ozen, Yesim Deniz (International Journal of Sustainable Construction Engineering and Technology, 2023)
Due to the decreasing resources in the world, different recycling applications in different sectors are gaining more importance. Urban transformations initiated especially for earthquake remnants and old buildings provide many advantages for the construction sector. Recycling of valuable materials from the wastes from each demolished construction site is very important in terms of costs. It is also important to analyse the effectiveness of both public and private companies to compare different approaches and illustrate best practices. From this point of view, this research has been carried out on the recycling of construction and demolition wastes in Turkey and the performance of companies dealing with this business. Analytical hierarchy process (AHP) and gray relations analysis (GRA) will be applied for the evaluation phase. The criteria will be analysed through AHP and the connection between companies will be determined with the GRA method. According to the results, potential improvement opportunities will be identified to increase the performance and competitiveness of construction excavation companies. This will also allow the findings to serve as a potential model for other construction companies operating under different contingency factors, as well as presenting the list of criteria that construction companies should pay attention for performance evaluation.